On the accuracy of the approximation of composition of renewal processes by Poisson process - Grigelionis, B. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. О точности приближения композиции процессов восстановления пуассоновским процессомB. Grigelionis. Apie atstatymo procesų kompozicijos aproksimacijos Puasono procesu tikslumą